(untitled) (International Journal of Language, Literacy and Translation, 2019)
Written corrective feedback (WCF) is a form of feedback that is commonly employed pedagogically in writing class. However, providing corrective feedback on second language (L2) writing has received criticism for its ineffectiveness and demotivating effects on the students. Despite the criticism, WCF is still regarded as essential in L2 writing because studies have shown that WCF helps L2 learners improve their writing accuracy and performance. To increase the effectiveness of WCF, it is important for teachers to view the students' opinions on the WCF given by their teachers in the writing classes. This will help the teachers to develop the most effective strategy for students to understand the corrective feedback of the errors found in their writing. This is a preliminary study for the researcher's main study on WCF. It aims to elicit students’ opinion of teacher’s WCF in an L2 writing class. The data for the study is gathered using an adapted questionnaire used in Ferris, Liu, Sinha and Senna's study (2013) on WCF for individual L2 writers. This study is carried out with undergraduates in an English Language class in Universiti Malaysia Sabah. The findings of this study show that L2 students WCF to improve their writing accuracy because their grammar/language problems affect their writing. For these L2 students, the teachers' WCF helps them to identify and to correct the errors found in their writing. This study has an implication on planning a tailor-made writing class with the necessary and immediate needs of the students. This method of obtaining feedback is pertinent in providing insights to the teachers for conducting an effective writing session in an ESL context.